Exclusion of chromosome 9 helps to identify mild variants of acromesomelic dysplasia Maroteaux type. Issue 1 (1st January 2000) - Faivre, Laurence; Le Merrer, Martine; Megarbane, André; Gilbert, Brigitte; Mortier, Geert; Cusin, Veronica; Munnich, Arnold; Maroteaux, Pierre; Cormier-Daire, Valérie
Abstract : Acromesomelic dysplasia Maroteaux type (AMDM) is an autosomal recessive disorder belonging to the group of acromesomelic dysplasias. AMDM is characterised by severe dwarfism with shortening of the middle and distal segments of the limbs. An AMDM gene has recently been mapped to human chromosome 9p13-q12 by homozygosity mapping in four consanguineous families. Here, we show linkage of the disease gene to chromosome 9p13-q12 in four of five consanguineous AMDM families and its exclusion in a fifth family with two children affected with a mild form of the disease. This study suggests that genetic heterogeneity accounts for the variable clinical and radiological severity of AMDM.